Faktor-Faktor yang Mempengaruhi Kepuasan Konsumen dalam Upaya Meningkatkan Pembelian (Studi di Travel PT Anugrah Tanjung Tabalong) - Harlie, M. (Universitas Brawijaya, Indonesia, 2016)
Abstract: This study aims to determine: (1) perceptions influence on customer satisfaction on the service of PT. Anugerah Tanjung Tabalong; (2) actual performance influence on customer satisfaction on the service of PT Anugerah Tanjung Tabalong; (3) Customer expectations influence on satisfaction on the service quality of PT Anugerah Tanjung Tabalong; (4) Satisfaction influences on customer purchasing decisionsof PT Anugerah Tanjung Tabalong. This study was performed at PT Anugerah Tanjung Tabalong. The method used was descriptive quantitative. The population of this research was the service users of PT Anugerah Tanjung Tabalong.The study sample was 50 respondents by purposive sampling. Data collection was done by using survey and questionnaire. Data were analyzed usingmodel of Partial Least Square (PLS) with t-test using smart PLS version 2.0.M3 software. The result shows that: (1) consumer perceptions Affect the customer satisfaction amounted to 0.681 greater than loading value above 0.50, it means that there is significant influence perception variables on customer satisfaction on PT Anugerah Tanjung Tabalong Travel; (2) the actual performance influence customer satisfaction is 0.823 greater than loading value above 0.50, it means that there is a significant influence ofÂ behaviour variable toward the quality of service of PT Anugerah Tanjung Tabalong; (3) the customer expectation which influences the customer satisfaction is 1.054 greater than loading value above 0.50, it means that there is a significant influence customer expection variable on costumer satisfaction of PT Anugerah Tanjung Tabalong Travel. The results showed that the existence of significant influence between customer perception, actual performance, and customer expectation on customer satisfaction that may in turn increase consumer purchases at PT Anugerah Tanjung Tabalong Travel.